Analysis on scalability and energy efficiency of HEVC decoding using task-based programming model - Georgakarakos, Georgios; Holmbacka, Simon; Lilius, Johan (The 2016 Conference on Design & Architectures for Signal & Image Processing : Rennes, France, October 12-14, 2016, 2016)
In this paper we evaluate the impact of task programming model in scalability and energy efficiency of dynamically parallel applications like HEVC decoding. We develop a task-based parallel HEVC decoding implementation supporting Tiles and Wavefront Parallel Processing. We measure and compare thread-based HEVC decoding against its alternative version supporting task-based parallelism. Results show that the task programming model can improve scalability and energy efficiency of HEVC decoding for various parallel application parameters (task dependencies, task granularity) and computing platforms ranging from server to laptop and embedded environments.